Effect of Non-Modified as Well as Surface-Modified SiO2 Nanoparticles on Red Blood Cells, Biological and Model Membranes - Solarska-Ściuk, Katarzyna; Męczarska, Katarzyna; Jencova, Vera; Jędrzejczak, Patryk; Klapiszewski, Łukasz; Jaworska, Aleksandra; Hryć, Monika; Bonarska-Kujawa, Dorota (International journal of molecular sciences, 2023)
Nanoparticles are extremely promising components that are used in diagnostics and medical therapies. Among them, silica nanoparticles are ultrafine materials that, due to their unique physicochemical properties, have already been used in biomedicine, for instance, in cancer therapy. The aim of this study was to investigate the cytotoxicity of three types of nanoparticles (SiO2, SiO2-SH, and SiO2-COOH) in relation to red blood cells, as well as the impact of silicon dioxide nanoparticles on biological membranes and liposome models of membranes. The results obtained prove that hemolytic toxicity depends on the concentration of nanoparticles and the incubation period. Silica nanoparticles have a marginal impact on the changes in the osmotic resistance of erythrocytes, except for SiO2-COOH, which, similarly to SiO2 and SiO2-SH, changes the shape of erythrocytes from discocytes mainly towards echinocytes. What is more, nanosilica has an impact on the change in fluidity of biological and model membranes. The research gives a new view of the practical possibilities for the use of large-grain nanoparticles in biomedicine.
Keywords: Nanoparticles; erytrocyty; Erythrocytes; oxid křemičitý; nanočástice; osmotic resistance; Cell Membrane; erythrocyte membranes; Silicon Dioxide; liposomes; erythrocytes; membrány; Membranes; silica nanoparticles; biological membranes; hemolytic toxicity; buněčná membrána